Effectiveness of ertugliflozin during Ramadan fasting in patients with type 2 diabetes mellitus: a real-world study (ErtuRamadan study) - Pathan, Md Faruque; Akter, Nazma; Mustari, Marufa; Saifuddin, M.; Sharifuzzaman, Mirza; Rahman, Mohammad Motiur; Ripon, Mohammed; Mohiuddin, S. M.; Kamrul-Hasan, A. B. M.; Hannan, Mohammad Abdul; Alam, Muhammad Shah; Mahjabeen, Samira; et al. (Frontiers in Endocrinology, 2025)
BackgroundManagement of type 2 diabetes mellitus (T2DM) during Ramadan fasting presents unique challenges due to prolonged fasting periods, irregular meal schedules, and altered medication timing, potentially impacting glycemic control. Ertugliflozin, a sodium-glucose co-transporter 2 (SGLT2) inhibitor, has been shown to improve glycemic control in T2DM effectively. However, the effectiveness of ertugliflozin during Ramadan fasting, a period with unique glycemic challenges, has not been studied extensively.MethodsThis study was a multicenter, real-life experience study involving 1373 adult patients with known T2DM for at least one year, an HbA1c level of less than 10%, and who intended to fast during Ramadan. Participants were divided into two groups: the Ertu group (n=703), consisting of patients who had been on a stable dose of ertugliflozin for at least three months before Ramadan, and the non-Ertu group (n=670), which included patients receiving other oral antihyperglycemic drugs (OADs) except ertugliflozin. Patients attended a baseline visit one month before the first day of Ramadan and a follow-up visit within one month after the last day of Ramadan. Both visits included history taking, physical examinations, and laboratory tests. The primary endpoints were changes in HbA1c levels, body weight, body mass index (BMI), and the incidence of hypoglycemia during Ramadan fasting.ResultsThe mean age of the study participants was 50.37 ± 11.14 (SD) years, with 40.6% male and 58.7% female. Patients receiving ertugliflozin showed significant reduction in HbA1C (-0.65 ± 0.67% vs. -0.22 ± 0.64%, p<0.001), body weight (-1.24 ± 2.58 kg vs. -0.36 ± 3.41 kg, p<0.001), and BMI (-0.48 ± 1.03 kg/m² vs. -0.11 ± 1.33 kg/m², p<0.001) compared to the non-Ertu group. Hypoglycemia was reported in 0.3% of the ertugliflozin group and 0.7% of the other group, with comparable adverse events (p=.23; ≥0.05), indicating a favorable safety profile for ertugliflozin during fasting.ConclusionThis study demonstrates that ertugliflozin is effective and safe for patients with T2DM during Ramadan fasting.